PERIODONSIUM SEBAGAI WADUK SITOKIN DAN EFEKNYA - Ratih Larasati; I G A A Putu Swastini (Jurnal Kesehatan Gigi (Dental Health Journal), 2016)
Some studies show a link between periodontal disease and cardiovascular disease (CVD), and tooth loss may be associated with an increased risk of coronary heart disease and infective endocarditis. The relationship between the teeth and CVD can be explained by periodontal disease, caries, tooth extraction, changes in eating patterns following tooth loss, or other intruders. Oral and dental procedures incorrectly can cause bacteremia, namely the entry of microorganisms in the blood and circulate throughout the body. Patients with dental problems that has cardiovascular disease should take antibiotics before going to the dentist. The use of antibiotics prior to a dental procedure will reduce the possibility of being infected by the bacteria. Maintaining oral hygiene is highly recommended to avoid focal infection.